2021
DOI: 10.1002/aelm.202100082
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Integrated Ferroelectric Thin‐Film‐Transistor – Influence of Device Scaling on Threshold Voltage Compensation in Displays

Abstract: Thin‐film transistors (TFTs) based on amorphous indium‐gallium‐zinc‐oxide (a‐IGZO) have attracted vast attention for use in organic light‐emitting diode (AMOLED) displays due to their high electron mobility and large current on–off ratio. Although amorphous oxide semiconductors show considerably less threshold voltage (Vth) variation than poly‐silicon, large‐area processing and degradation effects can impede the characteristic parameters of a‐IGZO TFTs, which manifests in an uneven brightness distribution acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 50 publications
1
54
0
Order By: Relevance
“…Consequently, for mass production, this material system can easier be deposited via atomic layer deposition (by using a precursor ratio of 1:1) [6] or sputtering techniques. [47] ii) The crystallization in the FE phase can be achieved at low process temperatures of 300-400 °C, [13,[48][49][50] which is the lowest among all so far investigated dopants. [51] This is most likely due to the comparatively low crystallization temperature of ZrO 2 compared to other potential metal oxide dopants.…”
Section: Materials System Hzomentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, for mass production, this material system can easier be deposited via atomic layer deposition (by using a precursor ratio of 1:1) [6] or sputtering techniques. [47] ii) The crystallization in the FE phase can be achieved at low process temperatures of 300-400 °C, [13,[48][49][50] which is the lowest among all so far investigated dopants. [51] This is most likely due to the comparatively low crystallization temperature of ZrO 2 compared to other potential metal oxide dopants.…”
Section: Materials System Hzomentioning
confidence: 99%
“…In the literature, many studies can be found that optimize the HZO films with regard to the requirements mentioned above, for example, by using various film thicknesses and dopant concentrations. [13,[49][50][51][96][97][98] The first important parameter that can be tailored to optimize the crystallization temperature and the FE properties are thus the thickness of the HZO films. It is known from the literature that the crystallization temperature increase for ultrathin films (in the range of 5 nm and below) due to the surface energy effect.…”
Section: Ferroelectric Boel Memory Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most promising FE material to meet these requirements is zirconium-doped hafnium oxide (HZO) [4][5][6]. It crystallizes in the FE phase at about 350 °C and over a wide range of doping concentrations [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%